2013
DOI: 10.1074/jbc.m113.484840
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of the Plasmodium falciparum Erythrocyte-binding Antigen-175 (EBA175)-Glycophorin-A Interaction

Abstract: Background: The GYPA-PfEBA175 interaction is important for erythrocyte invasion by the malaria parasite.Results: The entire ectodomain of EBA175 interacted with GYPA with different biochemical parameters to the previously determined GYPA-binding fragment containing two DBL domains.Conclusion: Regions outside of the tandem DBL domains contribute to GYPA binding by EBA175.Significance: These findings may assist the design of an EBA175-based malaria vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 41 publications
3
52
0
1
Order By: Relevance
“…These results confirm that the acquisition of antibodies against placental parasites and then against VAR2CSA start developing as early as in first pregnancy (20,38,39) and highlight the importance of the N-terminal region of VAR2CSA (DBL1X-3X) in the development of the humoral response against PAM. This is borne out by other studies revealing the detailed mechanisms of other malaria-derived protein/ligand interactions (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 92%
“…These results confirm that the acquisition of antibodies against placental parasites and then against VAR2CSA start developing as early as in first pregnancy (20,38,39) and highlight the importance of the N-terminal region of VAR2CSA (DBL1X-3X) in the development of the humoral response against PAM. This is borne out by other studies revealing the detailed mechanisms of other malaria-derived protein/ligand interactions (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 92%
“…However, this hypothesis is inconsistent with a much earlier study by Orlandi et al (24) in which the binding of native PfEBA175 to human erythrocytes was observed to be potently inhibited by soluble Neu5Gc and oligosaccharides containing Neu5Acα2-3Gal but not by Neu5Ac as a monosaccharide. This glycan-binding specificity was confirmed in a recent biochemical investigation using a recombinant protein consisting of the entire ectodomain of PfEBA175 (25). Furthermore, the sialic acid specificity of PfEBA175 orthologs cannot explain the restriction of ape Laverania parasites to their respective chimpanzee and gorilla hosts, both of which carry a functional CMAH gene (5).…”
mentioning
confidence: 78%
“…By using SPR, we have been able to address the host specificity of EBA175-GYPA interactions in a quantitative and directly comparable manner by measuring binding affinities. The proposed lack of PfEBA175 binding to Neu5Gc, which forms the basis of the EBA175-related host restriction hypothesis, also is at odds with the observation that soluble Neu5Gc as a monosaccharide inhibits the binding of native PfEB175 to human erythrocytes with a level of potency similar to that of oligosaccharides containing Neu5Acα-2,3-Gal (24) and our recent finding that a functionally active recombinant protein containing the full-length ectodomain of PfEBA175 binds Neu5Gc as well as Neu5Acα-2,3-Gal (25). We attempted to investigate the specificity of the EBA175-GYPA interaction from the perspective of the host receptor, but we were unable to express human GYPA in a functionally active, recombinant form using our mammalian expression system (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1D is reproduced from Wanaguru et al . with minor stylistic changes [8]. Bars represent mean ± standard deviation (SD), n = 3.…”
Section: Resultsmentioning
confidence: 99%